2020
DOI: 10.1016/j.jpainsymman.2020.04.155
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ+ Inclusive Palliative Care in the Context of COVID-19: Pragmatic Recommendations for Clinicians

Abstract: As coronavirus disease 2019 (COVID-19) continues to impact the seriously ill and their families on a global scale, considerations given to marginalized groups amid the pandemic are essential to ensure the provision of high-quality and dignified care. Lesbian, gay, bisexual, transgender, gender-nonconforming, and queer/questioning-identified (LGBTQþ) persons are particularly vulnerable to health inequities across settings, including palliative care and at the end of life. There is a crucial gap in the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 14 publications
2
28
0
8
Order By: Relevance
“…Em relação às temáticas, duas categorias sintetizam os principais aspectos abordados nos estudos: "Estratégias para implementação dos cuidados paliativos no enfrentamento da COVID-19" (17)(18)(19)21,23,25,(27)(28)(29)(30)(31)(32)35,36,(38)(39)(40)(41)(42)44) (19; 63,3%) e "Terapêutica paliativista no contexto da pandemia: desafios e contribuições" (16,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)31,33,34,(36)(37)(38)(39)(40)(41)(43)(44)(45) (24; 80%).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Em relação às temáticas, duas categorias sintetizam os principais aspectos abordados nos estudos: "Estratégias para implementação dos cuidados paliativos no enfrentamento da COVID-19" (17)(18)(19)21,23,25,(27)(28)(29)(30)(31)(32)35,36,(38)(39)(40)(41)(42)44) (19; 63,3%) e "Terapêutica paliativista no contexto da pandemia: desafios e contribuições" (16,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)31,33,34,(36)(37)(38)(39)(40)(41)(43)(44)(45) (24; 80%).…”
Section: Resultsunclassified
“…(18,21,23,25,27,28,30-32,35,39,40,42,44 ou cuidadores. (23,26,34,40,41,(43)(44)(45) Os desafios estiveram relacionados ao acesso dos pacientes aos serviços de saúde, (26,34,36,44) às necessidade de capacitação dos profissionais, (26,27,29,33,36) à sobrecarga de trabalho e à falta de recursos, como retratado na figura 2. (26,36) Alguns estudos estão tanto na primeira quanto na segunda categoria, pois apresentaram informações pertinentes para ambas.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Previous experience with natural disasters suggests that marginalized groups experience substantially more negative consequences in times of natural disaster, which warrants enhanced support and advocacy. For example, LGBTQ+ individuals are at a disadvantage, both for greater risk of COVID-19 mortality 25 and poorer ABI related treatment, 12 such as “lack of specialized and knowledgeable screening, education, and treatment for reproductive health, sexuality, and sexual performance related issues.” 12 (p377) Although the current COVID-19 pandemic is certain to lead to many unknown and unanticipated outcomes in this and other groups, there are specific areas known to affect women and LGBTQ+ individuals with ABI, namely IPV, social and financial disparities, and technological accessibility. Disparities in these domains can be expected to be exacerbated by the current state of the world and lead to further marginalization, making them critical to highlight as potential intervention targets.…”
mentioning
confidence: 99%
“…Reluctance to visit healthcare services for fear of discrimination which is higher among LGBTQ community is a definite barrier for proper screening, early diagnosis and prompt treatment for COVID-19. In many cases their palliative/end-of-life care may be compromised amidst systemic inequality, health disparity and marginalization [ 8 ]. Moreover, it has been observed that sexual minority group possesses lower perceived susceptibility to COVID-19, lesser worry about the pandemic and are less likely to undertake hygienic measures than heterosexuals [ 9 ].…”
mentioning
confidence: 99%